The Effect of Renewable Energy on Energy Import Dependence: An Empirical Analysis in Turkey - İbrahim Ürkmez; Mete Cüneyt Okyar (Siyasal: Journal of Political Sciences)
Energy import dependency has remained one of the most important problems of countries that cannot meet their energy needs from domestic sources from past to present. Countries with insufficient resources in terms of fossil energy sources have met their energy demand through imports. This situation has caused countries to become dependent on external resources. For this reason, Turkey’s energy import dependency has increased continuously; according to the data published by EUROSTAT as of 2018, Turkey is foreign-dependent with approximately 74%. This situation has brought the issue of energy supply security to the agenda in Turkey. For this reason, it is important to examine Turkey’s energy import dependency and to propose solutions according to the results obtained. In this study, the effect of renewable energy sources on energy import dependency in Turkey during 1990-2018 was analyzed using the ARDL bounds test approach. The working results have determined that renewable electricity production, GDP per capita, urban population growth, and world natural gas prices have a statistically significant effect on energy import dependency. World oil prices were not statistically significant. As a result, renewable energy production reduces energy import dependency, while the most important determinant is GDP per capita.